2009
DOI: 10.1007/s12206-008-1210-2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of a binary gas flow inside a rotating cylinder

Abstract: A new approach to calculate the axially symmetric binary gas flow is proposed. Dalton's law for partial pressures contributed by each species of a binary gas mixture (argon and helium) is incorporated into numerical simulation of rarefied axially symmetric flow inside a rotating cylinder by using the time relaxed Monte-Carlo (TRMC) scheme and the direct simulation Monte-Carlo (DSMC) method. The results of flow simulations are compared with the analytical solution and results obtained by Bird [1]. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For Poiseuille flow [14,15] and the gas flow within a circular cylinder [16][17][18], viscous effects dominate the system, and the gas does not compress much; therefore, we consider them to test the applicability of NSF.…”
Section: Resultsmentioning
confidence: 99%
“…For Poiseuille flow [14,15] and the gas flow within a circular cylinder [16][17][18], viscous effects dominate the system, and the gas does not compress much; therefore, we consider them to test the applicability of NSF.…”
Section: Resultsmentioning
confidence: 99%
“…Their study indicated that the density, velocity and temperature profiles, obtained from the TRMC method, are in excellent agreement with the ones from the DSMC method. Moreover, Ganjaei and Nourazar (Ganjaei and Nourazar 2009) studied binary Argon and Helium mixture flow inside a rotating cylinder using the DSMC and TRMC methods. They used Daltons law for partial pressures of each species and showed that the results of TRMC method are in excellent agreement with the results obtained from analytical solution and standard DSMC method.…”
Section: Introductionmentioning
confidence: 99%